Analisis Kepuasan Mahasiswa Terhadap Kualitas Pelayanan pada Politeknik kent Bogor Tahun 2009 - Yuli Anwar; Syamsul Anwar (Jurnal Ilmiah Binaniaga, 2009)
Quality and customer satisfaction are closely related, the quality of giving a boost to consumers to establish a very strong bond with the company. In the long term bond like this allows companies to thoroughly understand the expectations which the firm maximizes the consumer’s experience of fun and minimize or eliminate unpleasant experience. Because customer satisfaction in turn can create customer loyalty or loyalty to companies that provide satisfactory service quality.    The value of service quality performance variables are 143-286, with the average value of 3.31 or assessment the position is quite satisfied. While the assessment of service expectations variable is between 240-294, with the average value of 3.91 or assessment on the position on an important value. Picture of student satisfaction with the service by the Politeknik KENT Bogor can be seen from the diagram on the Cartesian Quadrant II which containts the attributes that have given satisfaction to the students.    These are attributes that must be maintained so that student satisfaction is always achievied (a) The building is owned by adequale, (b) The appearance and comfort of the lobby, (c) Clean and tidy room lecturers, (d) Clean and comfortable classrooms, (e) Officers can provide timel, (f) Officers are always ready willing to help in times of need, (g) the officer did not show the impression busy in welcoming the arrival of students, (h) officers always instill confidence in students, (i) the officer behaved in providing services, and (j) students feel secure to do transactions with the institution.